Population growth and infant mortality - Christina Fabella (University of the Philippines, School of Economics (UPSE), 2008)
The relationship between population growth and economic outcomes is an issue of great policy significance. In the era of the Millennium Development Goals, poverty and its correlates have become the compelling issues. Economic growth may not automatically translate into reductions in poverty and its correlates (may not trickle down) if income distribution is at the same time worsening. We therefore investigate the direct effect of population growth on infant mortality for various income categories of countries. We find that after controlling for other relevant influences, population growth robustly increases infant mortality five years later across income categories. The coefficient for population growth and its significance rise as we move from full sample to lower-income to lowincome categories. The adverse effect of population growth on infant survival thus rises as one moves from full sample, to lower-income to low-income categories. For low-income countries, the adverse effect of population growth emerges sooner, i.e., after two years. The study highlights the important, if delayed, contribution of population control programs to reduction in infant mortality and poverty.
Keywords: 330; Bevölkerungswachstum; Kindersterblichkeit; Bevölkerungspolitik; Millennium Development Goals